Bridging the Gap Between Health Psychology and Philosophy: An Existential Approach to Promoting Physical Activity - St Quinton Tom; Morris Ben (Sciendo, 2019)
Participation rates in a number of health-related behaviors, such as physical activity, have shown recent declines. To promote participation, psychological health behavior change theories have been developed to understand and help identify relevant psychological processes. Such processes can then be targeted within interventions utilizing specific behavior change techniques (BCTs). Although the use of these theories and BCTs is useful in facilitating change, such work could be enhanced through the inclusion and consideration of philosophical positions. Existentialism suggests that the absurdity and meaningless of human life allows the individual to create their own meaning within a behavior. This philosophical position thus places meaning and individual purpose at the center of human behavior. The purpose of this article is to connect the theoretical insights and BCTs outlined within health psychological behavior change theories with the philosophical position of existentialism. The integration of this philosophical position, and potentially many others, with psychological ideas may provide useful insights into the promotion of health-related behaviors.